Comparação entre a rigidez vascular dos pacientes idosos com e sem fibrilação atrial - Dorneles, Michelle Caixeta Naves (2018)
Introduction: Like arterial stiffness, atrial fibrillation (AF) may result from factors such as systemic arterial hypertension and age. The aim of this study was to compare the arterial stiffness in elderly individuals with and without incidental AF and to determine the associations of systemic arterial pressure and age with arterial stiffness in elderly individuals with AF. Methods: This was an retrospective cohort study and a total of 23 elderly patients with AF (GAF) were selected. The control group was divided into three subgroups, with 23 participants each, matched for systolic blood pressure (GI), age (GII) or both blood pressure and age (GIII). Data were collected from the EVOPIU database. Arterial stiffness was measured by the carotid to femoral pulse wave velocity (cfPWV). Results: In the comparative analysis, cfPWV did not differ for groups with similar ages (GAF: 10.2 ± 1.8 m/s vs GII: 10.7 ± 1.2 m/s, p = 0.147; GAF: 10.2 ± 1.8 m/s vs GIII: 10.2 ± 1.3 m/s, p = 0.955). However, cfPWV was higher among GAF patients than among younger patients (GAF: 10.2 ± 1.8 m/s vs GI: 8.9 ± 1.1 m/s, p < 0.05). In the multivariate analysis, age was significantly associated with arterial stiffness even in the presence of systemic arterial hypertension in elderly individuals with atrial fibrillation. Conclusion: Arterial stiffness is similar in elderly individuals with and without atrial fibrillation when matched for age and blood pressure. Age appears to be the main determinant of arterial stiffness.